A multicenter, randomized, active‐controlled study to investigate the efficacy and safety of intravenous ferric carboxymaltose in patients with iron deficiency anemia. Issue 2 (17th June 2013) - Onken, Jane E.; Bregman, David B.; Harrington, Robert A.; Morris, David; Acs, Peter; Akright, Bruce; Barish, Charles; Bhaskar, Birbal S.; Smith‐Nguyen, Gioi N.; Butcher, Angelia; Koch, Todd A.; Goodnough, Lawrence T.
<x xml:space="preserve">Abstract</x> Background Many patients receiving oral iron for iron deficiency anemia (IDA) cannot tolerate or fail to respond to therapy, and existing intravenous (IV) iron formulations often require repeated administrations. Ferric carboxymaltose (FCM), a nondextran IV formulation, permits larger single doses. Study Design and Methods We evaluated FCM versus oral iron in IDA patients. After 14 days of oral iron, 507 participants responding inadequately to oral iron (hemoglobin [Hb] increase <1 g/dL; Cohort 1) were assigned to Group A (two doses of FCM, 750 mg, 1 week apart) or Group B (oral iron, 325 mg, 3 × day for 14 additional days). Also, 504 subjects not appropriate for oral iron (Cohort 2) were assigned to Group C (FCM as above) or Group D (standard‐of‐care IV iron). The primary efficacy endpoint was change to highest observed Hb from baseline to Day 35. The composite safety endpoint included all‐cause mortality, nonfatal myocardial infarction, nonfatal stroke, unstable angina, heart failure, arrhythmias, and hyper‐ or hypotensive events. Results Mean (± standard deviation [SD]) Hb increase was significantly greater in Group A–FCM than Group B–oral iron: 1.57 (±1.19) g/dL versus 0.80 (±0.80) g/dL (p = 0.001). Post hoc comparison of Group C–FCM and Group D–IV standard of care also demonstrated significant mean (±SD) increase in Hb from baseline to highest value by Day 35 in Group C versus Group D: 2.90 (±1.64) g/dL versus 2.16 (±1.25) g/dL (p = 0.001). Safety endpoints occurred in 17 of 499 (3.4%) participants receiving FCM versus 16 of 498 (3.2%) in comparator groups. Conclusion Two 750‐mg FCM infusions are safe and superior to oral iron in increasing Hb levels in IDA patients with inadequate oral iron response.